STUDY ON RISING OF YOGI ADITYANATH AND SURVEY ON PEOPLE’S PERCEPTION ON HIS STYLE OF ADMINISTRATION AND GOVERNANCE - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana (The journal of contemporary issues in business and government, 2021)
This article focuses on the present Chief Minister of Uttar Pradesh, Adityanath Yogi, and tries to contrast his political actions with his background as a member of the Shaiva sect of the Nath Yogis. After tracing the recent history of the Gorakhpur monastery he leads, researchers have focused on Adityanath‘s mode of power. The survey is conducted to know people’s perception of the Yogi government, Mentioning his last and often controversial actions and declarations. The survey was conducted in Gorakhpur, UP, and found that people are satisfied and pleased with the functioning and implementation of government policies in the current political landscape. Lastly, people urge to retain the same government in future also.